Dams, Terrorism, and Water Nationalism’s Response to Globalization and Development: The Case of South Asia - Ashraf, Tamanna (Terrorism and political violence, 2022)
Building on a global research sweep of terrorist organizations’ (as well as other non-state actors such as separatist and insurgent groups) use of fresh water as a target, weapon, or source of control, this paper analyzes attacks on major water projects (specifically dams and other related infrastructure) in South Asia—the region identified to have had the largest number of recorded water-related violent incidents. Focusing on India, Pakistan, and Afghanistan, and the post 9/11 period through 2019, the paper explores how large water infrastructures (and their environs) have become hot spots for violence between states that use water development projects to consolidate power, garner local loyalty, and create a national narrative and non-state actors who attempt to target these same projects to assert indigenous self-determination, subvert state power, or challenge state authority through terrorist means. Since fresh water is shared across borders, dam projects can become entangled in regional political disputes further exacerbating violent conflict between state and non-state actors. Given its impacts on water resources, climate change may act as a “threat multiplier” by enhancing local grievances, providing both government and terrorist groups additional incentives for exploitation, and further contributing to instability. The analysis provided here borrows from and contributes to the fields of development, environment and security, and terrorism studies.